(untitled) (Bangladesh Journal of Psychiatry, 2020)
Both genetic and environmental factors including parenting style are responsible for the causation of schizophrenia. A young adult developed delusion regarding alien as well as some characters of the computer games he used to play. Later he was diagnosed with schizophrenia. There was evidence of intrafamilial conflict with lack of good relationship with father. His introverted nature, lack of social interactions and some irrelevant behavior were found as being reinforced by her mother. There may be an association of schizophrenia with parenting style which may be modifiable. Bang J Psychiatry June 2018; 32(1): 22-23